Autism & Gluten: The Proof By Regression! - Hakim Rahmoune; Nada Boutrid (Pediatric Neurology Briefs Publishers, 2018)
Investigators from different clinical and research centers from Paris, France studied the polymorphisms of the HLA class II loci in an autistic population.